2018
DOI: 10.1016/j.joca.2018.02.113
|View full text |Cite
|
Sign up to set email alerts
|

T1ρ and T2 of articular cartilage after acl injury predict patient-reported outcomes at 3 years after acl reconstruction

Abstract: Purpose: Osteoarthritis (OA) is one of the leading causes of long-term pain and disabilities associated with musculoskeletal disorders. Effective treatment and disease-progression slowdown depend on early detection and quantification of risk. However, current disease parameters, like joint space width (JSW), have proven to be insufficient for the prediction of OA. The purpose of the present study was to investigate if combining fractal-and entropy-based bone texture analyses with joint space width (JSW) and jo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…All full-text manuscripts were retrieved and screened, with 11 studies meeting the inclusion criteria [21][22][23][24][25][26][27][28][29][30][31]. Twenty conference abstracts also met the criteria and, as per Cochrane recommendations [32,33], can be found in Supplementary File 3 [34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53]. Excluded studies can be found in Supplementary File 4, with the two most common reasons for exclusion being participant age outside the specified range and time to follow-up within a year from injury.…”
Section: Resultsmentioning
confidence: 99%
“…All full-text manuscripts were retrieved and screened, with 11 studies meeting the inclusion criteria [21][22][23][24][25][26][27][28][29][30][31]. Twenty conference abstracts also met the criteria and, as per Cochrane recommendations [32,33], can be found in Supplementary File 3 [34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53]. Excluded studies can be found in Supplementary File 4, with the two most common reasons for exclusion being participant age outside the specified range and time to follow-up within a year from injury.…”
Section: Resultsmentioning
confidence: 99%
“…The 3D MAPSS CW-T 1ρ sequence has been widely used to evaluate tissue degeneration and monitor compositional changes longitudinally in the MSK system. [31][32][33][34][35][36] Some of the sequence features in 3D MAPSS, such…”
Section: Discussionmentioning
confidence: 99%
“…The 3D MAPSS CW‐T 1ρ sequence has been widely used to evaluate tissue degeneration and monitor compositional changes longitudinally in the MSK system 31–36 . Some of the sequence features in 3D MAPSS, such as magnetization reset, phase modulation, and VFA scheme, 23 have been successfully incorporated in the PM‐UTE‐AdiabT 1ρ sequence.…”
Section: Discussionmentioning
confidence: 99%